2015
DOI: 10.1165/rcmb.2015-0207rc
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increased Prevalence of Asthma and Nasal Polyps in Chronic Rhinosinusitis and Its Association with Altered IL-6 Trans-Signaling

Abstract: We report that S100 proteins were reduced in patients with chronic rhinosinusitis (CRS). S100A8/9, which is important in epithelial barrier function, was particularly decreased in elderly patients with CRS. Epithelial expression of S100A8/9 is partly regulated by the IL-6 trans-signaling pathway. The goal of this study was to investigate whether or not age-related reduction of S100A8/9 in CRS is associated with blunting of IL-6 trans-signaling. The levels of IL-6, soluble IL-6 receptor (sIL-6R), soluble gp130 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
1
45
2
1
Order By: Relevance
“…The odds of AENSS‐Sx‐Pur declined with higher ages, excluding the current long‐term CRS status group, possibly due to differential susceptibility to viral infections which precede bacterial infections and decrease with increasing age . Yet, individuals with long‐term CRS may be at risk of developing viral respiratory infections even at older ages due to compromised epithelial barrier function, which can accompany CRS, suggestive of a disease progressive model in those with persistent CRS.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of AENSS‐Sx‐Pur declined with higher ages, excluding the current long‐term CRS status group, possibly due to differential susceptibility to viral infections which precede bacterial infections and decrease with increasing age . Yet, individuals with long‐term CRS may be at risk of developing viral respiratory infections even at older ages due to compromised epithelial barrier function, which can accompany CRS, suggestive of a disease progressive model in those with persistent CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that CRS exhibited an age‐related decline in innate barrier function in eosinophilic nasal polyps (ENP), and an age‐related decrement in neutrophilic inflammation in non‐eosinophilic nasal polyps (NENP), which reflected treatment outcomes in elderly NENP subjects . Interestingly, elderly CRS patients were characterized by increased neutrophilic proinflammatory cytokines such as IL‐1ÎČ, IL‐6, IL‐8, and TNF‐ɑ and by less responsiveness to steroid treatment in a recent study .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sIL-6R plays an important role in the responses mediated by IL-6. The activity of sIL-6R is implicated in a variety of inflammatory diseases, such as inflammatory bowel disease (Brulhart et al, 2010;Rose-John et al, 2009), rheumatoid arthritis (Febbraio et al, 2010) and asthma (Robinson et al, 2015;Ullah et al, 2015;Cho et al, 2015), and there are anti-IL-6R therapies, which target sIL-6R as well as the membrane-bound mIL-6R (Mima & Nishimoto, 2009). …”
Section: Introductionmentioning
confidence: 99%